Airborne pollen calendar of Portugal: a 15-year survey (2002–2017) - Camacho, Irene (2021)
Data about the occurrence of airborne pollen enables the creation of pollen calendars with an approximation of flowering periods for the most common allergenic plant species in a specific area. The aim of this work is to provide pollen calendar for each of the seven monitoring regions of Portugal based on 15 years of airborne sampling, in order to chart the seasonal behaviour of the main allergenic pollen types.